Iris and ciliary body cysts and phakic intraocular lenses - Gharaibeh, A M; Liehneova, I; Mojzis, P; Ziak, P; Alió, Jorge L (European journal of ophthalmology, 2020)
Phakic intraocular lenses are used to correct refractive errors. The procedure is predictable and potentially reversible. The procedure is not free of complications though. The occurrence of iris cyst after implantation of a phakic intraocular lens was not described previously in the literature. We describe two cases of iris cysts in the presence of a phakic intraocular lens; the first case describes a cyst which was not present prior to the anterior chamber phakic intraocular lens implantation. The second case describes a hidden iris cyst that affected the posterior chamber phakic intraocular lens position and lead to glaucoma.
Keywords: dospělí; Cysts; myopie; Female; Ciliary Body; nemoci duhovky; Adult; ženské pohlaví; Uveal Diseases; iris cyst; lidé; Iris Diseases; nemoci uvey; cysty; Slit Lamp Microscopy; corpus ciliare; glaucoma; Phakic Intraocular Lenses; Male; vyšetření štěrbinovou lampou; Lens Implantation, Intraocular; Myopia; mužské pohlaví; complications; implantace nitrooční čočky; zraková ostrost; Visual Acuity; fakické nitrooční čočky; Phakic intraocular lens; Humans